1988
DOI: 10.1017/s0890037x0003027x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Control of Japanese Honeysuckle (Lonicera japonica)

Abstract: Japanese honeysuckle (Lonicera japonicaThunb. # LONJA) vines can smother young trees, presenting problems in nursery, parkland, and woodlot management. The tardy-deciduous nature of honeysuckle provides an application window for its selective control with glyphosate [N-(phosphonomethyl)-glycine] or dichlorprop [(±)-2-(2,4-dichlorophenoxy)propanoic acid] plus 2,4-D [2,4-dichlorophenoxy)acetic acid] immediately after fall defoliation of hardwood species. Glyphosate at 1.5% v/v (5.4 g ae/L) applied in December ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Escort at 1 oz/acre applied May to August or Roundup i 0.75-percent solution applied September to October (Edwards and Gonzalez 1986Regeher and Frey 1988, Schmeckpeper and others 1987.…”
Section: Control Of Problem Plants During Site Preparationmentioning
confidence: 99%
“…Escort at 1 oz/acre applied May to August or Roundup i 0.75-percent solution applied September to October (Edwards and Gonzalez 1986Regeher and Frey 1988, Schmeckpeper and others 1987.…”
Section: Control Of Problem Plants During Site Preparationmentioning
confidence: 99%
“…It shows within the current forested landscape that Japanese honeysuckle is nearing its potential maximum distribution, with most of the lowland area vulnerable to invasion. Since this species is known to reduce species diversity (Bell et al, 1988;Davison and Forman, 1982), alter understory conditions (Barden and Matthews, 1980;Davison and Forman, 1982) and to suppress seedlings (Cain, 1991;Regehr, 1988;Schierenbeck, 2004), it is useful of managers to be able to assess the invasion probability of any given forest stand and identify areas of most issue for management action.…”
Section: Discussionmentioning
confidence: 99%
“…It can alter the understory and herbaceous layers of the communities it invades (Barden and Matthews, 1980;Davison and Forman, 1982) and ensure its continued dominance through the suppression of seedlings (Regehr, 1988;Schierenbeck, 2004). It also poses a threat to commercial forestry, as it has been shown to suppress seedlings of commercially valuable pine species (Cain, 1991).…”
Section: Study Speciesmentioning
confidence: 99%
“…He recommended careful application of glyphosate or Crossbow (triclopyr and 2,4-D combination) at this time of the year, but the latter may be more persistent. Note, however, that Regehr and Frey (1988) reported that applications of glyphosate or dichlorprop plus 2,4-D were less effective when the leaves were senescing in December. Cain (1984) found that hexazinone (Velpar L) was more effective than amitrol (Amitrol T) or mechanical cutting over a 3-yr study in all-aged loblolly-shortleaf pine stands in Arkansas, but the trees had to be protected from the application and multiple applications were required.…”
Section: Hybridsmentioning
confidence: 97%
“…Lonicera japonica is also problematic along railway rights-of-way (Regehr and Frey 1988) and in field borders and hedges (Warbach 1953;Gunning 1964). Shankman (1986) found that L. japonica covered abandoned fields shortly after the cessation of cultivation on loess bluffs in western Tennessee, yet it was replaced by continuous forest canopy within three decades.…”
mentioning
confidence: 99%